2008
DOI: 10.1590/s0103-64402008000100012
|View full text |Cite
|
Sign up to set email alerts
|

Human enamel nanohardness, elastic modulus and surface integrity after beverage contact

Abstract: This study evaluated nanohardness, elastic modulus and surface roughness of human enamel after contact with citric beverages. Human enamel samples were assigned to 3 groups according to the type of beverage used: carbonated drink, orange juice and tap water (control). Surface roughness was assessed using a profilometer, and nanohardness and elastic modulus were recorded using a nanoindenter. The pH of the beverages was measured before and after citric contact during 5 weeks. Means(SD) were as follows: Carbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
4
20
0
4
Order By: Relevance
“…The surface roughness of both the enamel and cementum also increased with time following exposure to the test solutions. The increase in surface roughness of enamel was in accordance with the study conducted by Machado et al (14). On clinical examination we found that at the end of ten days the enamel showed a softened opaque surface similar to the study reported by Fujji et al wherein the enamel surfaces placed in coca-cola and orange juice were visibly roughened and had lost their lustre (9).…”
Section: Discussionsupporting
confidence: 91%
“…The surface roughness of both the enamel and cementum also increased with time following exposure to the test solutions. The increase in surface roughness of enamel was in accordance with the study conducted by Machado et al (14). On clinical examination we found that at the end of ten days the enamel showed a softened opaque surface similar to the study reported by Fujji et al wherein the enamel surfaces placed in coca-cola and orange juice were visibly roughened and had lost their lustre (9).…”
Section: Discussionsupporting
confidence: 91%
“…However, one should bear in mind that such result may not hold for other methods used to measure erosion. In fact, in terms of wear, evidence exists that bovine dentin can be considered an acceptable substitute for human counterparts (15), at least from an in vitro study which though may not reflect the clinical reality (20).…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The nanoindenter is capable of applying loads of just few mNs while simultaneously measuring displacement changes <1 nm, hence accounting for both plastic and elastic deformation, as well as time dependent effects. [36][37][38][39][40][41] Bao et al 42 and Oyen 43 investigated, using nanoindentation, the relationship between 3 parameters, namely, elastic modulus, hardness, and recovery resistance for solids and mineralized tissues. It was found that an inherent relationship existed where the capacity of local energy dissipation or plasticity of a material could also be evaluated, and concluded that any one of the three parameters could be predicted if the other two were known.…”
Section: Introductionmentioning
confidence: 99%